Abandoned Land as a Paradox of Prosperity - Muhammad, Nur Regita Saputri; Nirwan Junus; Mohamad Rivaldi Moha (Yayasan Cahaya Generasi Positif, 2025)
Land in the context of human life is not merely a physical space, but also a social, economic, cultural, and political symbol that holds strategic functions for the sustainability of life. In the perspective of Indonesian agrarian law, land is positioned as a means to realize social justice as affirmed in Article 33 of the 1945 Constitution and the Basic Agrarian Law (UUPA). However, reality demonstrates that many lands are left uncultivated, giving rise to the phenomenon of abandoned land. This condition reflects a major paradox: on one hand, land is a fundamental and limited necessity, while on the other hand, land is often not utilized in accordance with its function. This research examines the conceptuality of abandoned land using a qualitative empirical approach, involving regional governments, the National Land Agency, village officials, and land certificate holders as informants. Research findings demonstrate that land abandonment is influenced by economic factors, ineffective policies, ownership disputes, and urbanization. In legal terms, abandoned land is considered a violation of the social function of land, whereby the state has the right to revoke land rights and return the land for public interest through a land administration mechanism. In conclusion, abandoned land is not merely an issue of land administration, but also a matter of social justice, economic sustainability, and environmental conservation. Proper handling through regulation, legal socialization, and community empowerment becomes the key to restoring land to its true function as a source of life and collective welfare.